The sacred body: asceticism in religion, literature, art, and culture - Jasper, David (Studies in Christianity and literature, 2009)
Continuing the work began in "The Sacred Desert", David Jasper here turns his attention to the body, seeking a profound understanding of what it means to be in the flesh. A deeply autobiographical journey through disparate written texts (in literature, philosophy, theology and religion), art, and cinema, "The Sacred Body" rigorously and artfully pursues the body of the Christian tradition of `the Word made flesh` - a body torn and crucified, resurrected, and divinised, embracing both deep suffering and profound joy. Engaging ascetic traditions that began among fourth-century desert monastics, as well as George Herbert, Simone Weil, Meister Eckhart, James Joyce and others, David Jasper once again provides a bold, learned, and original theological exploration.